Changes in cecal environment and forage intake of horses fed increasing amounts of starch - Eickleberry, Caitlyn R.; Ochonski, Patricia; Halpin, Michael Y.; Sorensen, Rachel J.; Lattimer, James M. (My University, 2019)
A limited body of research suggests the upper limit of small intestinal starch digestion is 2 to 4 g/kg BW starch/meal; however, the effect of increasing levels of starch on the cecal environment remains relatively unknown. The objectives of this study were to determine the effect of titrating levels of corn starch on the cecal environment and voluntary forage dry matter intake (VFDMI). Six cecally cannulated Quarter horses (8 to 13 yr; 524 ± 65.5 kg BW) were used in a dose titration style design. On d -14, horses were provided ad libitum Smooth Bromegrass hay and a ration balancer (0.0125% BW 4 times/d). On d 0, cecal digesta samples were collected for baseline measurements. On d 1, pelleted corn (69.4% starch) was offered at 0.5 g starch/kg BW/meal. Cecal sampling protocol was repeated on d 7 and every 7 d thereafter. Every 8 d thereafter, corn was increased to provide an additional 0.5 g starch/kg BW/meal until horses were offered 3.5 g starch/kg BW/meal. Feed refusals were recorded on d 6 and 7 of each treatment period. Cecal digesta was analyzed for pH and volatile fatty acids (VFA). Data were analyzed as a randomized complete block design with fixed effect of treatment and random effect of horse. As starch consumption increased VFDMI decreased (P ≤ 0.0001), similar to what has been previously described in ruminants. Effect of treatment was observed (P ≤ 0.032) with pH being lowest and VFA greatest when feeding 2.0 g/kg BW/meal. Starch consumption ≥ 2.0 g/kg BW/meal may lead to shifts in microbial communities and impaired fermentative activity, as characterized by decreased total VFA. Prior to popular belief, cecal acidosis was not observed for horses consuming ≥2.0 g starch.
Keywords: Spring 2019